Cochlear implantation in children with complex needs: the perceptions of professionals at cochlear implant centres. (November 2015) - Archbold, Sue; Athalye, Sheetal; Mulla, Imran; Harrigan, Suzanne; Wolters-Leermakers, Nina; Isarin, Jet; Knoors, Harry
Abstract : Objective: To explore the views of cochlear implant centre teams about the process of referral, assessment and rehabilitation for children with complex needs. Methods: An on-line survey of cochlear implant centres in the UK and in the Netherlands was carried out, with both quantitative and qualitative questions. The survey was designed and piloted by four professionals in each country, experienced in working in cochlear implant services, and with complex children. The open qualitative responses were analysed independently for the emergent themes. Results: Seven centres from Netherlands and eight from UK responded. The proportion of children reported with complex needs ranged from under 10% to between 40 and 60%. Children with complex needs were more likely to be later referred than the norm, and to take longer to assess. There was little agreement about the assessments used prior to implantation, or in follow-up. The most commonly seen additional disability was visual, followed by motor/physical challenges and autistic spectrum disorders. The most reported challenge was assessment, followed by parental expectations, and wearing the system. The least reported concern was educational management. The major goal was seen to be hearing and sensory input, rather than speech and language attainment. All centres commented on the importance of parental observation. Conclusion: There is a need for a consensus on the assessment of these children, with the development of more objective parent led observation measures to collect long-term data across centres. Closer collaboration with educators, particularly those with other expertise, would facilitate long-term management and asssessment. Data logging, now available, will help monitor wearing and use of system.